UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VII F MTS MA’ARIF NU 1 WANGON MELALUI PEMBELAJARAN IDEAL PROBLEM SOLVING - Fika Elfiani (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2017)
This research aimed to improve students’ creative thinking skill on the topic of tabular side ofgeometric shape by IDEAL Problem Solving Learning. The subject of this research was thestudents of class VIIIF in MTs Ma’arif NU 1 Wangon totaled to 40 Students. This researchwas a class action research that had been done in 3 cycles where each cycle consisted ofplanning, action, observation, evaluation, and reflection. The data of students’ creativethinking skill in this showed that there were improvements in each cycle. The average ofsmooth thinking indicator in cycle I was 2,78, in cycle II 3,2, and in cycle II 2,38, and 2,53 incycle III. The average of flexible thinking indicator in cycle I was 2,5, in cycle II 2,38, and2,53 in cycle III. The average of original thinking indicator in cycle I was 2,5, in cycle II 2,53,and 2,98 in cycle III. The average of elaborating skill indicator in cycle I was 2,35, in cycle II2,7, and 3,28 in cycle III. It could be concluded that IDEAL Problem Solving was able toimprove students’creative thinking skill on mathematic subject in class VIIIF MTs Ma’arifNU 1 Wangon.KEY WORDS: creative thinking skill, IDEAL Problem Solving